Effects on the quality of frozen-thawed alpaca (Lama pacos) semen using two different cryoprotectants and extenders - Santiani, Alexei (2005)
Aim: To evaluate two extenders and two cryoprotectant agents (CPA) for alpaca semen cryopreservation. Methods: Semen samples were obtained from four adult alpacas (Lama pacos) and frozen using extender I (TRIS, citrate, egg yolk and glucose) or extender II (skim milk, egg yolk and fructose), each containing either glycerol (G) or ethylene glycol (EG) as CPA. Consequently, four groups were formed: 1) extender I-G; 2) extender I-EG; 3) extender II-G; and 4) extender II-EG. Semen was diluted in a two-step process: for cooling to 5 °C (extenders without CPA), and for freezing (extenders with CPA). Viability and acrosome integrity were assessed using trypan blue and Giemsa stains. Results: When compared, the motility after thawing was higher (P < 0.05) in groups II-EG (20.0 % ± 6.7 %) and II-G (15.3 % ± 4.1 %) than that in groups I-G (4.0 % ± 1.1 %) and I-EG (1.0 % ± 1.4 %). Viable spermatozoa with intact acrosomes in groups II-EG (18.7 % ± 2.9 %) and II-G (12.7 % ± 5.9 %) were higher than that in groups I-G (5.7 % ± 1.5 %) and I-EG (4.0 % ± 1.0 %). Conclusion: The skim milk- and egg yolk-based extenders containing ethylene glycol or glycerol to freeze alpaca semen seems to promote the survival of more sperm cells with intact acrosomes than the other extenders.